Young learners' response processes when taking computerized tasks for speaking assessment. (April 2018) - Lee, Shinhye; Winke, Paula
We investigated how young language learners process their responses on and perceive a computer-mediated, timed speaking test. Twenty 8-, 9-, and 10-year-old non-native English-speaking children (NNSs) and eight same-aged, native English-speaking children (NSs) completed seven computerized sample TOEFL ® Primary™ speaking test tasks. We investigated the children's attentional foci on different test components (e.g., prompts, pictures, and a countdown timer) by means of their eye movements. We associated the children's eye-movement indices (visit counts and fixation durations) with spoken performance. The children provided qualitative data (interviews; picture-drawings) on their test experiences as well. Results indicated a clear contrast between NNSs and NSs in terms of speech production (large score differences) as expected. More interestingly, the groups' eye-movement patterns differed. NNSs tended to fixate longer on and looked more frequently at the countdown timer than their NS peers, who were more likely to look at content features, that is, onscreen pictures meant to help with building up speech. Specifically, the NNSs' fixations on timers were likely to co-occur with hesitation phenomena (e.g., hemming; pausing; silence). We discuss (a) the potential effects of test-specific features on children's performance and (b) child-appropriate test accommodations and practices.